2016
DOI: 10.3390/ijms17040527
|View full text |Cite
|
Sign up to set email alerts
|

Bavachin from Psoralea corylifolia Improves Insulin-Dependent Glucose Uptake through Insulin Signaling and AMPK Activation in 3T3-L1 Adipocytes

Abstract: The fruit of Psoralea corylifolia L. (Fabaceae) (PC), known as “Bo-Gol-Zhee” in Korea has been used as traditional medicine. Ethanol and aqueous extracts of PC have an anti-hyperglycemic effect by increasing plasma insulin levels and decreasing blood glucose and total plasma cholesterol levels in type 2 diabetic rats. In this study, we purified six compounds from PC and investigated their anti-diabetic effect. Among the purified compounds, bavachin most potently accumulated lipids during adipocyte differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…24) Furthermore, bavachin was reported to exhibit direct effect on Akt phosphorylation. 11,57) In this study, we showed that Mfn2 ablation by the siRNA resulted in the inhibition of phosphor-Akt, and inhibition of phosphorAkt also aggravated bavachin-induced ER stress (Fig. S1).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…24) Furthermore, bavachin was reported to exhibit direct effect on Akt phosphorylation. 11,57) In this study, we showed that Mfn2 ablation by the siRNA resulted in the inhibition of phosphor-Akt, and inhibition of phosphorAkt also aggravated bavachin-induced ER stress (Fig. S1).…”
Section: Discussionmentioning
confidence: 59%
“…8,9) It has been ever reported that bavachin is a potential estrogen supplement for estrogen replacement therapy because of the osteoblastic activity. 10,11) However, as a "double-edged sword," bavachin could also cause obvious adverse effects. Both our early work and latest articles suggested that endoplasmic reticulum (ER) stress and related signal pathways might play an important role in bavachin-induced hepatotoxicity.…”
mentioning
confidence: 99%
“…[4,5] In addition, bavachin is considered as a cholesterol acyltransferase inhibitor (IC 50 = 86 µM), which has the therapeutic potential for type II diabetes by activating insulin signal pathways and AMPK activation in 3T3-L1 adipocytes. [6,7] Furthermore, bavachin is also a useful remedy (IC 50 = 4.89 µM) for inflammatory activity through inhibiting IL-6-induced STAT3 activation and phosphorylation. [8] Moreover, bavachin is reported as a neuraminidase inhibitor with IC 50 value of 44.79 µM.…”
Section: Introductionmentioning
confidence: 99%
“…It accumulates in the adipocytes and can activate different adipogenic transcription factors, including CCAAT/enhancer binding protein-α (C/EBPα) and peroxisome proliferator-activated receptor-gamma (PPARγ). It can alter the cellular glucose uptake by modulating the activity of GLUT-4 and the activity of pAKT as well as AMPK regardless of the presence of insulin [159]. Different bioactive isoflavones from chickpea are also reported to regulate the expression of GLUT-4, and along with this, those phytochemicals can also alter the expression of the acidbinding protein (ap2), uncoupling protein-2 (UCP-2), and lipoprotein lipase (LPL) in pre-adipocytic cells (3T3-L1 cells) [160].…”
Section: Rosmentioning
confidence: 99%